The Relationship Between Long-Term Usage Of Hormonal Contraception And Sexual Dysfunction And Quality Of Women's Sexual Life - Sabatina Windyaningrum; Dwi Murwani K.W.M. Justus K.W.M. Justus; Wenny Rahmawati Rahmawati (Media Husada Journal of Midwifery Science, 2025)
Long-term use of hormonal contraception is suspected to have side effects, decreasing women's libido,thus affecting their sexual function and quality. Experts call this sexual dysfunction. This study aims todetermine the relationship between long-term use of hormonal contraception and sexual dysfunction andthe quality of women's sexual lives at TPMB Mudjiasri. The study was conducted from August toNovember 2024. The research method used an analytical observational approach with a cross-sectionalapproach. A sample of 30 people was drawn using total sampling that met the inclusion and exclusioncriteria. Statistical tests used univariate and bivariate Spearman Rank analysis. The results showed that12 respondents (40%) had used hormonal contraception for 3-6 years, 10 people (33.3%) had used it formore than 6 years up to 9 years, and 8 people (26.7%) had used hormonal contraception for more than9 years. Furthermore, of the 30 respondents, 93.3% (28 people) experienced sexual dysfunction and 6.7%(2 people) did not experience sexual dysfunction. In addition, 83.3% (25 people) had an unsatisfactoryquality of sexual life and 16.7% (5 people) had a satisfactory quality of sexual life. The correlation testusing Spearman Rank obtained a p-value of 0.112 in the relationship between the duration of hormonalcontraceptive use and sexual dysfunction, which means there is no relationship between the twovariables. In addition, no significant relationship was found between the duration of hormonalcontraceptive use and the quality of women's sexual life with a p-value of 0.416. The duration of hormonalcontraceptive use does not directly affect the state of sexual dysfunction and the quality of a woman'ssexual life. In addition, the causes of sexual dysfunction experienced by acceptors can be influenced byseveral factors, including age, occupation, knowledge, social environment, and communication, whichstill require further in-depth research. The conclusion of this study is that there is no relationship betweenthe duration of hormonal contraceptive use and sexual dysfunction and the quality of women's sexual life.